2010
DOI: 10.1262/jrd.09-088k
|View full text |Cite
|
Sign up to set email alerts
|

Temporal and Spatial Regulation of Let-7a in the Uterus During Embryo Implantation in the Rat

Abstract: Abstract. Mammalian embryonic implantation requires reciprocal interactions between implantation-competent blastocysts and a receptive uterus. Some microRNAs might play a key role during embryo implantation in the mouse, but the let-7a expression profiles in the rat uterus during peri-implantation are unknown. In the study, the expression of let-7a in the uterus during early pregnancy, pseudopregnancy, artificial decidualization and activation of delayed implantation was detected by Northern blotting and in si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 34 publications
0
24
0
Order By: Relevance
“…In all mammals, P4 is required for maternal support of conceptus survival and development, as well as for the establishment of endometrial receptivity for blastocyst implantation and maintenance of endocrine homeostasis by inhibiting the secretion of gonadotropin [10,11,30]. Studies have demonstrated that miRNAs in the endometrium could be regulated by steroid hormones [6,10,11,13,30]. The let-7 miRNA was originally identified in C. elegans as a regulator of developmental timing and cell proliferation [31].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In all mammals, P4 is required for maternal support of conceptus survival and development, as well as for the establishment of endometrial receptivity for blastocyst implantation and maintenance of endocrine homeostasis by inhibiting the secretion of gonadotropin [10,11,30]. Studies have demonstrated that miRNAs in the endometrium could be regulated by steroid hormones [6,10,11,13,30]. The let-7 miRNA was originally identified in C. elegans as a regulator of developmental timing and cell proliferation [31].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have indicated that Bsg is capable of inducing the expression of a range of MMPs, including MMP-1, MMP-2, MMP-3, . It was found that Bsg was expressed highly in the luminal and glandular epithelial cells in rat and mouse endometria on day 1 of gestation and decreased gradually until day 5 [10,11]. However, Bsg was shown to be strongly expressed in the primary decidua on day 6, and the expression level was significantly higher in the implantation sites than in the interimplantation sites [16,17].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study demonstrated temporal and spatial regulation of let-7a and miR-320 that were differentially expressed in the rat uterus with expression affected by decidualization during the window of embryo implantation. 72,73 Additionally, a subset of miRNAs (hsa-miR-222, 221, 181b, 27b, 29b, 507, 143, 101, 30d, 30c and 23a) participates in gene reprogramming during endometrial stromal cell (ESC) decidualization in vitro and hsa-miR-222 was found to play a key role in differentiation of ESCs by regulating their terminal withdrawal from the cell cycle. 74 In our laboratory, studies on spontaneous fetal loss in pigs have provided evidence of selective miRNA expression in endometrial lymphocytes (unpublished data).…”
Section: Micrornas and Immune Cells At The Maternal-fetal Interfacementioning
confidence: 99%
“…49 Taken together, miRNA regulation of angiogenesis participates in both pathological and physiological angiogenesis, and offers a novel therapeutic avenue to explore. Let-7a and miR-320 72,73 Uterine miRNAs…”
Section: Microrna Regulation Of Angiogenesismentioning
confidence: 99%